The Predictive Value of CHADS-VASC Score in No-Reflow Phenomenon in Primary Percutaneous Coronary Intervention - Farahe, Ali; Samore, Naseer Ahmed; Ali, Azhar; Shafique, Hafiz Muhammad; Tariq, Muhammad Naeem; Shabbir, Saddaf; Kamran, Javeria; Azad, Naseem (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To determine the role of CHADS-VASc Score in predicting No Reflow phenomenon in STEMI patients undergoing primary PCI. Study Design: Analytical cross-sectional study.Place and Duration of Study: This study was carried out at a Tertiary Cardiac Care Center from Feb to May 2022.Methodology: A total of (n = 320) patients who underwent PPCI at Armed Forces Institute of Cardiology from 4th February to 3rd May 2022 were enrolled in this study. Patients were divided into 2 groups, Comparision group with no NRP and NRP group. Descriptive statistics was run to present the categorical data in frequencies and percentages and continuous data in Mean±SD. Chi square test was applied to compare both groups regarding categorical and continuous variables. CHADS-VASc score was also compared in both groups.Results: Out of (n=320) patients, 80(25%) patients developed NRP. Age, Diabetes, LV EF, history of stroke or TIA, peripheral arterial disease, TIMI thrombus grade, total stented length and CHADS-VASc score were found to be significantly associated with NRP. Binary logistic regression analysis revealed diabetes, LV EF, TIMI thrombus grade, total stented length and CHADSVaSc score to be independent predictors of NRP.ROC analysis revealed a cutoff CHADS-VaSc score of 3 to be a good predictor of NRP (sensitivity 65% and specificity 82%). Conclusion: CHADS-VASc score can be an important pre PCI tool to predict NRP during primary PCI.